Chinese Administrative Reforms: A Replica or Derivative of the Western NPM Model?. Issue 1 (June 2017) - Zhang, Mengzhong; Holzer, Marc
At the theoretical level in the public administration community, there is an ongoing debate as to whether public administration principles can be universally applied to any country or whether they are bounded by political, economic, social, cultural, historical, environmental and traditional factors. While there is an increasing observation in the 21st century that convergence of administrative reforms between developing and developed countries has great momentum, this paper argues that national context plays a significant (if not vital) role in a specific country's administrative reforms. To put this argument in context, the paper examines similar and dissimilar features of Chinese administrative reforms with that of USA, with a conclusion that Chinese administrative reform is not a replica, but rather a derivative, of the Western NPM Model.